THE IMPLEMENTATION OF 21 ST CENTURY SKILLS AS THE NEW LEARNING PARADIGM TO THE RESULT OF STUDENT’S CAREER AND LIFE SKILLS - - Sulistyaningsih; Kani Sulam; Abdul Syakur; Lailatul Musyarofah (Magister Scientiae, 2019)
Teaching students to learn and to work well with 21st century skills is not only the domain of vocational school (SMK), but also general senior high school (SMA/MA) as well. It is not enough for students to have only core skills in literacy and numeracy in order to succeed as individuals, citizen, or workers. This article deliberates how to implement the 21st century skills as the new learning paradigm for senior high school students. Furthermore, how the result of those implementations to the student’s career and life skills is based on the five elements as the indicators. For the first research question, the study was descriptive and qualitative. For the second research question, the study was descriptive and quantitative. The writers did an observation, which is workplace action research. There is a Career and Life Skills Program for the twelfth grade students of MA NU Walisongo Sidoarjo. The indicators included in the scoring result sheet consist of the five elements of skills that comprise the Career and Life Skills (CLS) domain. They are (1) flexibility and adaptability skills; (2) initiative and self-direction skills; (3) social and cross-cultural skills; (4) productivity and accountability skills; and (5) leadership and responsibility skills. The result of those implementations to the student’s career and life skills based on its five elements is quite good. At the end, they are expected will be job-ready with the skills most in demand in the 21st century.